Endovascular repair of acute vs. subacute uncomplicated type B aortic dissection: a systematic review and meta-analysis - Zhao, WenXin; Yang, Yang; Wu, ZhiYuan; Chen, ZuoGuan; Diao, YongPeng; Lan, Yong; Li, YongJun (Frontiers in Cardiovascular Medicine, 2023)
Abstract: This study aimed to conduct a meta-analysis evaluating the optimal timing for endovascular repair of acute versus subacute uncomplicated Type B Aortic Dissection. PubMed, EMBASE, Wed of Science and Cochrane Library was interrogated to identify Electronic bibliographic studies updated to January 2023 to collect studies compared the clinical outcomes of endovascular repair for Acute Versus Subacute Uncomplicated Type B Aortic Dissection. Data were aggregated as pooled odds ratios (OR) using the fixed or random effects models according to the significance of heterogeneity， Pooled odds ratios (OR) were calculated by RevMan 5.3 and applied with fixed or random-effect models. A comprehensive literature search found 322 citations published and finally among them 6 studies containing 3,769 patients (acute group 2,642, subacute group 1,127) were included in review. There is an increased risk of 30-day complications (OR=1.51,95%CI,1.26-1.81）30-day mortality (OR=2.39,95%CI, 1.55-3.67) and 1-year mortality (OR=1.47,95%CI, 1.12-1.94) for an acute uTBAD group compared to subacute ones. Similarly, reintervention was more likely in the acute group than in the subacute group (OR=1.46,95% CI, 1.09-1.97). However, no significant differences were found in long-term mortality. This meta-analysis confirmed that there was no significant difference in the long-term prognosis between the acute and subacute phases in the timing of surgery. However, considering the high incidence of complications, high re-intervention rate and one-year mortality probably caused by high intima fragility in the acute phase, endovascular repair at subacute phase appears to favorably compare with acute strategy. But future studies with adequate patient numbers and longer-term follow-up are necessary to further verify the study conclusion.